The development of household-scale biogas technology from organic waste in Lasah Village, Karangploso District - Saefullah, Lalu; Ardiyanto Darmanto; Dedy Pradigdo; Farit Hendro Wibowo; Akhmad Ali Imron (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Climate change and limited conventional energy resources have pushed to utilize renewable energy. One of them is the development of household-scale biogas technology from organic waste. This Community Service Study (PKM) aims to document and analyze the socialization process of household-scale biogas applications in Lasah Village, Karangploso District, Kab. Poor. The activities carried out are, socialization about the benefits of biogas, the production process, and the operation of the system. Community involvement from the planning stage to implementation. The impact of socialization is assessed through surveys, interviews and observations of community participation and understanding. The study results show an increase in public understanding of the benefits of using biogas and a positive response to socialization and public interest in adopting this technology. It can be concluded that the socialization of the use of biogas technology on a household scale has been well received. Collaboration between researchers and the community can overcome communication barriers and provide practical guidance on the implementation of biogas technology. Although there is still a way forward in terms of system maintenance and management, this initial step provides a strong foundation for further development. It is hoped that this study will provide valuable insights for similar efforts in other areas, as well as encourage the implementation of sustainable technology for a brighter future.